2022
DOI: 10.1155/2022/5719897
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Learning and Microscopic Imaging in the Nursing Process of Neurosurgery Operation

Abstract: Neurosurgery is mainly for the treatment of head trauma, cerebrovascular disease, brain tumors, and spinal cord disorders. These operations are difficult and risky, so disability and mortality are high. To reduce the risk of surgery, reduce postoperative complications, and improve the treatment effect of patients, this article applies deep learning and microscopic imaging to the nursing process of neurosurgery. Through deep learning and microscopic imaging, doctors can learn about patients during surgery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Such developments supply additional proof that optimal performance can be obtained via deep architecture (Deepalakshmi et al, 2021;Waleed et al, 2021). The CNN-based image recognition models have been capable of distinguishing a considerable number of targets, and the obtained recognition accuracies exceed the standard individual's level (Jiang, 2022). Therefore, it can be concluded that, deep CNN can be exploited for realizing such developments also in the COVID-19 discrimination too.…”
mentioning
confidence: 89%
“…Such developments supply additional proof that optimal performance can be obtained via deep architecture (Deepalakshmi et al, 2021;Waleed et al, 2021). The CNN-based image recognition models have been capable of distinguishing a considerable number of targets, and the obtained recognition accuracies exceed the standard individual's level (Jiang, 2022). Therefore, it can be concluded that, deep CNN can be exploited for realizing such developments also in the COVID-19 discrimination too.…”
mentioning
confidence: 89%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%